Sword 1 and 2: Subgroup Analysis of 48 Week Results by Age, Race and Gender. (4th October 2017) - Walmsley, Sharon; Richmond, Gary; Bredeek, Fritz; Ramgopal, Moti; Hung, Chien-Ching; Blair, Elizabeth; Kahl, Lesley; Underwood, Mark; Angelis, Kostas; Vandermeulen, Kati; Wynne, Brian; Aboud, Michael
Abstract: Background: Switching to the 2-drug regimen (2DR) of DTG+RPV was proven non-inferior to continuing a suppressive PI-, INI- or NNRTI- based current antiretroviral regimen (CAR) at Week 48. This analysis evaluated the efficacy and safety of switching from CAR to DTG+RPV by age, race and gender subgroups. Methods: Two identically designed, open-label, multicenter, global, phase III, non-inferiority studies compared the efficacy and safety of switching from a 3 or 4-drug CAR to DTG + RPV once daily in HIV-1-infected adults, with HIV-1 RNA<50 c/mL. Primary endpoint was proportion of patients with VL<50 c/mL at Wk48 using FDA Snapshot. Additional analysis were performed to summarize efficacy base on age, race and gender subgroups for each individual study and pooled. Results: 1024 patients were randomized and exposed (DTG+RPV 513; CAR 511), across both studies. Treatment arms were well matched for demographic and baseline characteristics. Median age across both arms was 43.4 years, with 29% and 28% ≥ 50 years in DTG+RPV and CAR, respectively. 23% and 21% were female while 18% and 22% were non-white for DTG+RPV and CAR. For the pooled studies and for SWORD-1 and SWORD-2 individually, switching to DTG+RPV was non-inferior to CAR at Wk48. Similar response rates were observed in the DTG+RPV arm compared with CAR across subgroups (Table 1). More AEs were reported in the DTG+/RPV arm across all subgroups except Asian race; no unexpected AEs were identified for either drug. Conclusion: Switch to a novel, once daily 2DR of DTG+RPV in patients with a suppressed viral load, was an effective and well tolerated treatment option across age, race, and gender subgroups which were consistent with overall results. Disclosures: S. Walmsley, Merck: Board Member, Consultant, Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; ViiV Healthcare: Board Member, Consultant, Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; Gilead Sciences: Board Member, Consultant, Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; GSK: Board Member, Consultant, Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; Janssen: Board Member, Consultant, Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Grant recipient, Research grant and Speaker honorarium; BMS: Grant Investigator, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; G. Richmond, Viiv Healthcare: Investigator, Research support; F. Bredeek, ViiV Healthcare: Investigator and Scientific Advisor, Consulting fee and Research support; M. Ramgopal, viiv: Investigator, Consulting fee; C. C. Hung, Gilead Sciences: Board Member and Speaker's Bureau, Consulting fee and Speaker honorarium; ViiV: Board Member and Investigator, Consulting fee and Research support; Abbvie: Board Member and Investigator, Consulting fee and Research grant; Bristol-Myers Squibb: Investigator, Research support; Jassen: Board Member and Investigator, Consulting fee and Research support; E. Blair, ViiV Healthcare: Employee and Shareholder, Salary; L. Kahl, ViiV Healthcare: Employee and Shareholder, Salary; M. Underwood, ViiV Healthcare: Employee, Salary; K. Angelis, GlaxoSmithKline: Employee, Salary; K. Vandermeulen, Jansen: Employee, Salary; B. Wynne, ViiV Healthcare: Employee, Salary; M. Aboud, ViiV Healthcare: Employee, Salary